Effect of Nonionic Surfactants and HPMC F4M on the Development of Formulations of Neuro-EPO as a Neuroprotective Agent - Muñoz-Cernada, A.; Pardo-Ruiz, Z.; , V.Montero-Alejo; Fernández-Cervera, M.; Sosa-Testé, I.; Amaro, Daniel; C. García-Rodríguez, J. (Journal of Advanced Pharmaceutical Science And Technology, 2014)
The purpose of this study was to investigate the effect of cremophor RH-40 and polysorbate 80 with hydroxypropyl methylcellulose (HPMC) F4M on the development of formulations of intranasal erythropoietin with low sialic acid content (Neuro-EPO) as a neuroprotective agent. Parameters such as pH, osmolality, apparent viscosity, and protein concentration were controlled for minimizing the differences between formulations. All Neuro-EPO formulations showed similar behaviour in the physicochemistry quality control. However significant differences between formulations were observed in the permanent unilateral ischemia model. The formulations and the vehicles containing cremophor RH-40 showed higher neurotoxicity levels than those containing polysorbate 80 as a nonionic surfactant. Formulations containing HPMC F4M at 0.6% as a bioadhesive polymer showed higher levels of survival and better neurological status than those without the polymer. The formulations with polysorbate 80 and HPMC F4M showed a higher index of survival, smaller incidence of clinical signs of stroke, and similar behavior in the learning and the memory to the false injured animals used as control. These findings suggest that the intranasal pathway constitutes a safe and alternative route of access of the Neuro-EPO to the brain.
Keywords: erythropoietin; stroke; nasal delivery; cremophor RH-40; polysorbate 80; HPMC